Rationale for revascularization to improve prognosis in stable coronary artery disease: the data from ISCHEMIA trial - L. L. Bershtein; E. V. Zbyshevskaya; V. E. Gumerova (Российский кардиологический журнал, 2020)
Although myocardial revascularization is one of the most studied types of medical interventions, there is a heated discussion in cardiology about the feasibility and indications for it in patients with stable coronary artery disease (chronic coronary syndrome). The recently completed ISCHEMIA trial is the largest current study comparing conservative versus invasive strategies in this category of patients. The article discusses the rationale for revascularization to improve prognosis according to the ISCHEMIA trial.